THE RELATIONSHIP BETWEEN NUMERICAL ABILITY, LEARNING MOTIVATIONS, AND PARENTAL ATTENTION WITH MATHEMATICS LEARNING OUTCOMES OF STUDENTS OF SMP NEGERI 03 KALIBAWANG WONOSOBO - Fauzan Adi Saputra; Widayati Widayati (Universitas Ahmad Dahlan, 2017)
Many factors are associated with mathematics learning outcomes. Numerical ability, learning motivations, and parental attention were related to student learning outcomes. Therefore, this study aimed to determine whether there is a relationship between numerical ability, learning motivations, and parental attention with math learning outcomes of students class VII in even semester of SMP Negeri 03 Kalibawang Wonosobo in academic year 2015/2016. The population in this study were students of class VII in SMP Negeri 03 Kalibawang Wonosobo in the academic year 2015/2016 consisting of three classes, are class VII A, VII B, VII C, by the total of students by 69 students. Class VII B was selected as a sample class using random sampling techniques, consisting of 23 students. Data collection techniques are done with the test and questionnaire methods. Contest instruments using validity, reliability, and power difference. After that, analysis prerequisite tests including normality, independence, and linearity test. Data analysis for hypothesis testing using product-moment correlation analysand multiple linear regression analysis. The result showed that there is a positive and significant correlations between numerical ability, learning motivations, and parental attentions with math learning outcomes by multiple correlation coefficient (R) by 0,834 and regression equation = 36,6717 + 0,3497 X + 0,6172 X 0,4482 X3, the relative contribution of variable X1 by 47,612%, the relative contribution (SR) of variable X2 by 30,661%, and the relative contribution of variable X3 by 21,727%, with the multiple determine coefficient (R2) by 0,695, the effective contribution of variable X1 by 33,121%, the effective contribution of variable X2 by 21,330%, and the effective contribution of variable X3 by 15, 115%,